Introduction to steels : processing, properties, and applications - Angelo, P. C.; Ravisankar, B. (CRC Press, Taylor & Francis Group, 2019)
"The book briefly describes the structure, properties and applications of various grades of steel ... covering most of the important types of steels ... including iron-carbon diagram, heat treatment, surface hardening methods, effect of alloying, specific applications, selection of materials, case studies and so forth."--Zadní strana obálky
Keywords: metalurgie; ocel; metallurgy; steel; učebnice; textbooks